Changes in worship building landscapes 21st-century in Europe - Markova, Madara (Landscape Architecture and Art, 2024)
Worship building landscapes, like others, are changing. The aspects that are studied about worship building landscapes are also changing. This study aims to create a context for the changes in Latvian worship building landscapes in the 21st century, by exploring and examining what changes in worship building landscapes have been recorded in studies in the anglophone research literature in Europe. Relevant peer-reviewed articles published in scientific journals were searched in the literature database “Web of Sciences”. In research was identified 106 publications about worship building landscape practices, which included 51 about physical changes in today’s worship building landscape, and also 38 about church politics, 62 about practices connected to the church, and 11 about pilgrimage. A widely explored topic in research is landscape change from a broad perspective, examining the influence of political, social, economic, and migration factors. Publications also show a strong focus on planning challenges, shifts in landscape perception, and how these perceptions evolve about worship building landscapes. The construction of new worship buildings, however, remains a less commonly studied subject. In certain parts of Europe, more specialized topics have gained attention, such as ruins, the risks posed by natural disasters, geotourism, and the role of worship buildings as habitats for owl nesting and bat nurseries. Research papers on changes in worship buildings vividly illustrate the intricate patterns shaping their landscapes, drawing the interest of scholars from diverse disciplines. When planning the development of landscapes surrounding places of worship, a holistic perspective is crucial. Traditionally, the focus has been heavily on the architectural values of these sites. However, in the 21st century, a broader approach is emerging, integrating economic, social, and environmental considerations alongside architectural aspects.